2020
DOI: 10.1101/2020.08.17.254060
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Old Dog, New Tricks: Influenza A Virus NS1 andIn VitroFibrillogenesis

Abstract: The influenza NS1 protein is involved in suppression of the host immune response. Recently, there is growing evidence that prion-like protein aggregation plays an important role in cellular signaling and immune responses. In this work, we obtained a recombinant, influenza A NS1 protein and showed that it is able to form amyloid-like fibrils in vitro. Using proteolysis and subsequent mass spectrometry, we showed that regions resistant to protease hydrolysis highly differ between the native NS1 form (NS1-N) and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The use of electron atomic force microscopy, spectrophotometry with Congo red dye, and fluorimetry with thioflavin T dye demonstrated that the T-cell receptor core peptide (CP) and its homologous peptide G51 from the NS1 influenza virus (as was shown by us earlier [24]) can form amyloid-like fibrils in vitro. Additionally, peptide G51 can form heterooligomers with peptide CP and modulate its oligomerization.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…The use of electron atomic force microscopy, spectrophotometry with Congo red dye, and fluorimetry with thioflavin T dye demonstrated that the T-cell receptor core peptide (CP) and its homologous peptide G51 from the NS1 influenza virus (as was shown by us earlier [24]) can form amyloid-like fibrils in vitro. Additionally, peptide G51 can form heterooligomers with peptide CP and modulate its oligomerization.…”
Section: Discussionmentioning
confidence: 77%
“…The NS1 protein of the influenza virus is prone to structural polymorphism, which also provides its multifunctionality [51,53], but its ability to form amyloid-like fibrils in vivo has not yet been demonstrated. Previous data suggest that the 140-151 aa region of NS1 may serve as a potential amyloidogenic determinant of this protein [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stained protein bands were cut out, and tryptic hydrolyses were performed as described [44]. Mass spectra of tryptic peptides were registered as described in section 2.4.…”
Section: Protein Identification Using Maldi Msmentioning
confidence: 99%